2020
DOI: 10.1038/s41598-020-73861-z
|View full text |Cite
|
Sign up to set email alerts
|

Vascular density with optical coherence tomography angiography and systemic biomarkers in low and high cardiovascular risk patients

Abstract: We aimed to compare retinal vascular density in Optical Coherence Tomography Angiography (OCT-A) between patients hospitalized for acute coronary syndrome (ACS) and control patients and to investigate correlation with angiogenesis biomarkers. Patients hospitalized for an acute coronary syndrome (ACS) in the Intensive Care Unit were included in the “high cardiovascular risk” group while patients without cardiovascular risk presenting in the Ophthalmology department were included as “control”. Both groups had bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 46 publications
(58 reference statements)
0
25
0
Order By: Relevance
“…For instance, a sparse vascular network pattern that is detected in fundus color photography was associated with an increase in 10-year risk of cardiovascular mortality [34] . Individuals with acute coronary syndrome and those with lower ejection fraction had lower vascular density on OCT angiography scans [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a sparse vascular network pattern that is detected in fundus color photography was associated with an increase in 10-year risk of cardiovascular mortality [34] . Individuals with acute coronary syndrome and those with lower ejection fraction had lower vascular density on OCT angiography scans [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These quantitative parameters describe early retinal microvascular changes in systemic pathologies. Numerous previous studies found associations between abnormal OCTA-based retinal metrics and diabetes, neurodegenerative disease, and cardiovascular events [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 In addition, the quantitative description of retinal microvascularization was recently enhanced by the development of a new noninvasive technique: optical coherence tomography angiography (OCT-A). 3 It has been shown that quantitative retinal vascular characteristics in both fundus photographs with SIVA software and metrics of retinal vascular density with OCT-A are associated with patients’ systemic vascular alteration, 4 cardiovascular risk profile 5 , 6 and cardiovascular complications. 7 In addition, deep learning algorithms have been described for diabetic retinopathy detection, retinopathy of prematurity screening, grading of age-related macular degeneration, and glaucoma detection.…”
Section: Introductionmentioning
confidence: 99%